Clinical Utility of Biomarkers in Diagnosis and Management of High Grade Cervical Intraepithelial Neoplasia (HSIL) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Objective of the study: The increasing inter- and intra-observer variability in the diagnosis of CIN by histopathology has led to the advent of different biomarkers. The aim of this study is to evaluate Ki-67 and p16 INK4a marker in differentiating CIN lesions and the clinical utility of it in the management of high grade squamous intraepithelial lesions (HSIL).Materials and methods: This cross-sectional study has been carried out among the biopsy proved cases of CIN2 and CIN3 in which P16 and Ki-67 immunostain was performed in the Colposcopy clinic, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Department of Pathology, BSMMU respectively from 14-3-17 to 30-05-18. Thirty-two cases were incorporated in the study by purposive sampling. Data was analyzed using SPSS version 17.Results: Among 32 cases of HSIL, 25 were diagnosed as CIN 2 (78.13 %) and 7 cases as CIN 3 (21.87 %) by histopathology. All the cases were subjected to immunohistochemistry with P16 and Ki 67. Regarding the status of P16, it was found positive only in 32% cases of CIN 2 but in 100% cases of CIN 3. Similarly, Ki67 was found positive in 36 % of CIN2 cases but in all cases of CIN 3 lesions. Thus immunostain confirmed one third histopathologically diagnosed CIN 2 cases. On the other hand, all cases of CIN 3 were confirmed as HSIL with the immunostain. All the cases of CIN 2 were reviewed for consensus opinion. Only 8 (32%) cases of CIN 2 were both immunostain positive , the review diagnosis by consensus opinion was also CIN 2 in those cases. One case (4%) of CIN 2 was P16 negative but Ki 67 positive, which ultimately revealed as immature squamous metaplasia. Sixteen cases of CIN 2 were negative for both P16 and Ki 67. Among these, majority cases (52%) , consensus opinion revealed as CIN 1 and 12% cases as immature squamous metaplasia. Therefore, an HSIL diagnosed by histopathology could be false positive in a significant number of cases and overtreatment of a false positive CIN 2 lesion can affect future reproductive status, also have some psychological consequences and economic burden in the health sector.Conclusion: By using the biomarkers, overtreatment and undertreatment of CIN can be avoided. All cases of CIN 2 should be carefully dealt with either review of the slides by consensus opinion or by doing immunohistochemistry if facility is available.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 79-86